Duodenal gastric metaplasia and Helicobacter pylori infection in patients with diffuse nodular duodenitis - X.B. Li; Z.Z. Ge; X.Y. Chen; W.Z. Liu (Brazilian Journal of Medical and Biological Research, 2007)
Whether the regression of gastric metaplasia in the duodenum can be achieved after eradication of Helicobacter pylori is not clear. The aim of the present study was to investigate the relationship between H. pylori infection and gastric metaplasia in patients with endoscopic diffuse nodular duodenitis. Eighty-six patients with endoscopically confirmed nodular duodenitis and 40 control patients with normal duodenal appearance were investigated. The H. pylori-positive patients with duodenitis received anti-H. pylori triple therapy (20 mg omeprazole plus 250 mg clarithromycin and 400 mg metronidazole, all twice daily) for one week. A control endoscopy was performed 6 months after H. pylori treatment. The H. pylori-negative patients with duodenitis received 20 mg omeprazole once daily for 6 months and a control endoscopy was performed 2 weeks after treatment. The prevalence of H. pylori infection was 58.1%, and the prevalence of gastric metaplasia was 57.0%. Seventy-six patients underwent endoscopy again. No influence on the endoscopic appearance of nodular duodenitis was found after eradication of H. pylori or acid suppression therapy. However, gastric metaplasia significantly decreased and complete regression was achieved in 15/28 patients (53.6%) 6 months after eradication of H. pylori, accompanied by significant improvement of other histological alterations. Only mild chronic inflammation, but not gastric metaplasia, was found in the control group, none with H. pylori infection in the duodenal bulb. Therefore, H. pylori infection is related to the extent of gastric metaplasia in the duodenum, but not to the presence of diffuse nodular duodenitis.